Loop I/NPS Morphology Predictions in the Ultralong-wavelength Band - Yanping Cong; Bin Yue; Yidong Xu; Furen Deng; Jiajun Zhang; Xuelei Chen (The Astrophysical Journal)
Loop I/North Polar Spur (NPS) is the giant arc structure above the Galactic plane observed at radio wavelengths (≲10 GHz). There has been long-standing debate about its origin. While many people believe that it consists of nearby supernova remnants (SNRs), some others consider it as a giant bubble close to the Galactic Center (GC), associated with the Fermi Bubble and the eROSITA X-ray bubble. At ultralong wavelengths (wavelength ≳10 m or frequency ≲30 MHz), particularly below ∼10 MHz, the free–free absorption of the radio signal by diffuse electrons in the interstellar medium (ISM) becomes significant, resulting in different sky morphologies from those at higher frequencies. In this paper, we develop emissivity models for the two Loop I/NPS origin scenarios, and predict the Loop I/NPS morphology at ultralong wavelengths in both scenarios, taking into account the free–free absorption effect. We find that in the SNRs model, the full Loop I/NPS will still be a bright arc, even at ∼1 MHz. In the GC model, the arc is fully visible only above ∼3 MHz. While below this frequency, it is visible only at Galactic latitudes b  ≳ 30°; the b  ≲ 30° part becomes invisible due to the absorption by the ISM electrons between the GC and the Sun. The upcoming space missions aiming at ultralong wavelengths, such as the Discovering Sky at the Longest wavelength and the Farside Array for Radio Science Investigations of the Dark ages and Exoplanets, can potentially distinguish these two scenario and provide decisive information about the origin of the Loop I/NPS.